2021
DOI: 10.1002/ecy.3520
|View full text |Cite
|
Sign up to set email alerts
|

A penalized likelihood for multispecies occupancy models improves predictions of species interactions

Abstract: Multispecies occupancy models estimate dependence among multiple species of interest from patterns of co‐occurrence, but problems associated with separation and boundary estimates can lead to unreasonably large estimates of parameters and associated standard errors when species are rarely observed at the same site or when data are sparse. In this paper, we overcome these issues by implementing a penalized likelihood, which introduces a small bias in parameter estimates in exchange for a potentially large reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…While multispecies occupancy models require substantial amount of data to precisely estimate cooccurrence (Clipp et al 2021), integrated approaches can provide stronger inferences compared to an analysis of each dataset in isolation (Zipkin et al 2019. Our integrated multispecies occupancy model helped to overcome data scarcity and produced more precise estimations of co-occurrence probabilities than multispecies models using separated datasets (Supplementary materials).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While multispecies occupancy models require substantial amount of data to precisely estimate cooccurrence (Clipp et al 2021), integrated approaches can provide stronger inferences compared to an analysis of each dataset in isolation (Zipkin et al 2019. Our integrated multispecies occupancy model helped to overcome data scarcity and produced more precise estimations of co-occurrence probabilities than multispecies models using separated datasets (Supplementary materials).…”
Section: Discussionmentioning
confidence: 99%
“…To account for these issues, multispecies occupancy models have been developed to estimate occupancy probabilities of two or more interacting species while accounting for imperfect detection (Rota et al 2016b, Fidino et al 2019. One caveat of multispecies models is that they require substantial data for robust ecological inference (Clipp et al 2021). To overcome data scarcity, several authors have suggested to combine multiple datasets into an integrated modelling framework (see Kéry & Royle (2020), Chapter 10, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, for our study, the existence of other important variables or interacting species influencing the occurrence of bobcats, gray fox, or cottontail rabbits is unlikely, since their omission would have been reflected in a substantial lack of goodness of fit of the occupancy models (additional variation in the data that is not explained by the model (Kéry & Royle, 2015)). Moreover, the inclusion of additional species in the analyses might have affected the precision and performance of the occupancy models (Rota et al., 2016) because multispecies occupancy models require a large amount of information (sites and records) to correctly estimate conditional occupancy parameters (Clipp et al., 2021; Kéry & Royle, 2021). The sensitivity of multispecies occupancy models to sample size and the number of records has not been formally tested and therefore requires more studies to check model performance and ability to detect co‐occurrence patterns under different sampling scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…For both data types, initial modeling revealed problems with boundary estimates 91 . To address this, we fit all models using a penalized likelihood approach 91 , 92 .…”
Section: Methodsmentioning
confidence: 99%